Current productivity of the scallop ( Mizuhopecten yessoensis) plantations in the bights of the Ussuri Bay (Japan Sea) - Galina S. Gavrilova; Larisa N. Kim (Известия ТИНРО)
Dynamics of the scallop spat settling to collectors of marine farms in the Sukhodol Bay and Malye Kushi Bay (Ussuri Bay) in 2012-2014 is considered. In the Sukhodol Bay, the spat density was 225 ind./m2 in 2012 that is close to usual value, but only 31 ind./m2 in 2013. In the Malye Kushi Bay, both years of 2013 and 2014 were low-productive for the spat, with its density in 2.5 times lower than in the Sukhodol Bay. On the contrary, the number of starfish spat on collectors was extremely high in 2013 - up to 42 ± 3 ind./m2. Size and weight parameters of juvenile scallops and starfish on collectors had year-to-year changes, as well. The starfish grown in conditions of high density in the 2013 had relatively small diameter (45.9 mm on average) and weight (1.8 g on average) in the age 1 year (in 2014), whereas the starfish spat grown in the 2014 with the density lower in 5.5 times reached larger mean size (55.5 mm) and weight (3.3 g). The scallop spat harvest in the bights of the Ussuri Bay is assessed in 0.5-1.5 · 106 ind./hectare. In general, the spat settling in this area is less intensive than in the Posyet Bay, Vostok Bay, and Nakhodka Bay. Environmental conditions in the Ussuri Bay are not favorable for collection of juvenile scallops, so the technology of scallop cultivation should be adapted for this area.